When two quarrel, the third rejoices: Windfall FDI and the early winners of the Russian-Ukrainian war - Maximilian W. Dirks (RWI - Leibniz-Institut für Wirtschaftsforschung, 2025)
Geopolitical conflicts significantly reshape global investment patterns, potentially creating unexpected economic opportunities. Using the Russian invasion of Ukraine as a quasi-exogenous shock, this study estimates the impact of redirected foreign direct investment (FDI) flows on economic output in bloc-free countries following this major geopolitical event. Employing a Difference-in-Differences model using Orbis Crossborder investment data, the findings reveal a sharp decline in Western FDI into Russia and Russia-leaning countries, alongside a significant increase in cross-border investment in bloc-free nations, with Brazil, India, Mexico, and Saudi Arabia among the primary beneficiaries. Using a Bayesian VAR, I estimate that these windfall FDI have increased GDP in the recipient countries by up to 2 %, underscoring the economic benefits associated with geopolitical neutrality. – – Geopolitische Konflikte verändern die globalen Investitionsmuster erheblich und können unerwartete wirtschaftliche Chancen eröffnen. Die russische Invasion in die Ukraine bietet die Möglichkeit, die Auswirkungen umgeleiteter ausländischer Direktinvestitionen (FDI) auf die Wirtschaftsleistung blockfreier Länder im Zuge dieses bedeutenden geopolitischen Ereignisses zu untersuchen. Unter Verwendung eines Differenz-in-Differenzen-Modells und von Orbis-Daten zu grenzüberschreitenden Investitionen zeigen die Ergebnisse einen starken Rückgang westlicher FDI in Russland und russlandfreundlichen Staaten sowie einen deutlichen Anstieg der Investitionen in blockfreien Ländern. Zu den Hauptnutznießern zählen Brasilien, Indien, Mexiko und Saudi-Arabien. Mittels eines Bayesianischen VAR-Modells schätze ich, dass diese exogenen Direktinvestitionen das BIP in den Empfängerländern um bis zu 2% gesteigert haben - ein Befund, der die wirtschaftlichen Vorteile geopolitischer Neutralität unterstreicht.
Keywords: F21; F23; F51; 330; Foreign direct investment; geoeconomics; fragmentation